The leaders of Alash and the history of Abay studies (Herald of Journalism, 2016)
This article is dedicated to the history of Abay studies. The articles of first investigators as: A. Bokeykhanov, A. Baytursynov, M. Dulatov about Abay’s art-works are analyzed in this work as well as the role of «Kazakh» newspaper in the formation of the Abay studies. Those published materials that had not been included to the scientific turnover for a long period of time are objectively and thoroughly judged. The scientific depth of research papers of A. Bukeyhanov, A. Baitursynov, M. Dulatov are analyzed along with the identification of the key areas of Abay studies. Tremendous attention is paid to the historical and ideological conditions that had negatively effected the development of Abay-studies. The work displays the historical significance of A. Bukeylhanov’s article on the literary heritage of Abay. Particular attention is paid to the scientific views of A. Baytursynov, who first identified Abay as a person playing a primary role in the national spirit of the Kazakh. In general, the searches and scientific achievements of the first Abayinvestigator’s are observed and analyzed.
Keywords: Abay studies; «Kazakh» newspaper; the literary heritage of Abay; national spirit